2010
DOI: 10.1093/jjco/hyq232
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Paclitaxel Combining with Gemcitabine is an Effective and Safe Treatment for Advanced Breast Cancer Patients

Abstract: The combination of weekly gemcitabine and paclitaxel in patients with advanced breast cancer showed acceptable outcome and excellent toxic profiles. This therapeutic benefit could be achieved in any linage of patients with good performance status; earlier usage of this regimen can provide better result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Interestingly, we obtained similar results to those achieved with standard regimens administered to metastatic breast cancer patients but avoiding toxicity. Accordingly, the use of gemcitabine and carboplatin plus iniparib yielded a 56% OCB rate [25], while the administration of capecitabine and vinorelbine in HER2-negative patients reached a OCB rate of 70% [26] and the combination of paclitaxel with gemcitabine resulted in a 80% OCB rate [27].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we obtained similar results to those achieved with standard regimens administered to metastatic breast cancer patients but avoiding toxicity. Accordingly, the use of gemcitabine and carboplatin plus iniparib yielded a 56% OCB rate [25], while the administration of capecitabine and vinorelbine in HER2-negative patients reached a OCB rate of 70% [26] and the combination of paclitaxel with gemcitabine resulted in a 80% OCB rate [27].…”
Section: Discussionmentioning
confidence: 99%
“…Several small-size studies have confirmed the tolerability and efficacy of wGT. 7 9 Although similar efficacy was observed between wGT and triweekly GT in phase III trials, wGT is widely used in clinical practice due to its convenience in terms of dose adjustment and patient management. 10 12 …”
Section: Introductionmentioning
confidence: 78%
“…[10][11][12] Research on optimization of the dosage regimen of wGT is ongoing. Two regimens of wGT have been widely accepted and used in the real world after years of practice: the 28-day regimen (GT on days 1, 8, and 15, every 28 days) 7,[12][13][14][15] and the 21-day regimen (GT on days 1 and 8, every 21 days). [9][10][11][16][17][18] To the best of our knowledge, no study has investigated the difference between the two wGT regimens in terms of efficacy, safety, or patient preference.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the treatment and maintenance polychemotherapy used in breast cancer, the use of paclitaxel combined with gemcitabine has shown better results than monotherapy with paclitaxel [8], one of the options recommended as first-line treatment [7]. Currently, there is no consensus on the optimal duration of the doublet protocol for maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%